Sahajiyā cult of Bengal and Pancha Sakha cult of Orissa - Dāsa, Paritoṣa (Firma KLM, 1988)
Comparative study of the Vaishnava Sahajiyā cult of Bengal and the religion of Pañcasakhā (literary group), of the medieval Oriya poets: Balarama Dasa, Jagannatha Dasa, Ananta Dasa, Yasovanta Dasa, and Acyutananda Dasa